The Potential of High-Throughput DNA Sequencing of the Paranasal Sinus Microbiome in Diagnosing Odontogenic Sinusitis - Haider, Asad A; Marino, Michael J; Yao, William C; Citardi, Martin J; Luong, Amber U (Otolaryngology-head and neck surgery, 2019)
High-throughput DNA sequencing of the paranasal sinus microbiome has potential in the diagnosis and treatment of sinusitis. The objective of this study is to evaluate the use of high-throughput DNA sequencing to diagnose sinusitis of odontogenic origin. Case series with chart review. Single tertiary care academic medical center. A chart review was performed of DNA sequencing results from the sinus aspirates obtained under endoscopic visualization in 142 patients with sinusitis. The identification of any potentially pathogenic bacteria associated with oral flora in a sample was classified as a positive result for sinusitis of odontogenic etiology. The sensitivity, specificity, and predictive values of using high-throughput DNA sequencing to diagnose sinusitis of odontogenic etiology were determined, with the patient's computed tomography sinus scan as the reference standard. On computed tomography scans, an odontogenic source was determined by the presence of a periapical lucency perforating the schneiderian membrane. Seven of the 142 patients enrolled in this study had an odontogenic source based on computed tomography scans. Relative to this reference standard, high-throughput DNA sequencing produced a sensitivity of 85.7% (95% CI, 42.1%-99.6%), a specificity of 81.5% (95% CI, 73.9%-87.6%), a positive predictive value of 19.4% (95% CI, 13.1%-27.7%), and a negative predictive value of 99.1% (95% CI, 94.7%-99.9%). This study supports the use of high-throughput DNA sequencing in supplementing other methods of investigation for identifying an odontogenic etiology of sinusitis.